Ceria nanoparticles promoted the cytotoxic activity of CD8+ T cells by activating NF-κB signaling. (10th April 2019) - Tang, Shupei; Zhou, Lan; Liu, Zhenyu; Zou, Ling; Xiao, Minglu; Huang, Chunji; Xie, Zhunyi; He, Haiyang; Guo, Yanyan; Cao, Yi; Huang, Huang; Wu, Xiaoping; et al.
Abstract : CNP treatment promoted in vitro killing activity and in vivo viral clearance capacity of CTL cells. Abstract : Cytotoxic CD8 + T cells (CTLs) are crucial for controlling intracellular pathogens as well as cancer. However, how to promote the cytotoxic activity of CTL cells in vitro and in vivo remains largely unknown. On the other hand, ceria nanoparticles (CNPs) are widely used in biomedical fields, but the role of CNPs in CTL cells is still unclear. In this study, we found that the activated antigen-specific (P14) and nonspecific CD8 + T cells with CNP treatment both produced more cytokines, including interleukin-2 (IL-2) and tumor necrosis factor-α (TNF-α), and released more effector molecules, such as granzyme B and perforin, and then exhibited higher killing activity of P14 cells in vitro and stronger viral clearance capacity of CTL cells in vivo . Mechanistically, the activated P14 cells with CNP treatment inhibited the production of reactive oxygen species, and therefore promoted the activity of NF-κB signaling. Importantly, while the P14 cells were simultaneously treated by IMD-0354, a specific inhibitor of NF-κB signaling, the increases of IL-2 and TNF-α productions and granzyme B and perforin releases were remedied, and the P14 cells eventually exhibited the natural killing activity in vitro . Thus, our results demonstrated that CNP treatment promoted the cytotoxic activity of CTL cells and provide new ideas in the usage of CNPs and fascinating pharmacological potentials for clinical application, especially cancer immunotherapy.